1998
DOI: 10.1091/mbc.9.2.291
|View full text |Cite
|
Sign up to set email alerts
|

ProteinC-Mannosylation Is Enzyme-catalysed and Uses Dolichyl-Phosphate-Mannose as a Precursor

Abstract: C-mannosylation of Trp-7 in human ribonuclease 2 (RNase 2) is a novel kind of protein glycosylation that differs fundamentally from N-and O-glycosylation in the proteinsugar linkage. Previously, we established that the specificity determinant of the acceptor substrate (RNase 2) consists of the sequence W-x-x-W, where the first Trp becomes C-mannosylated. Here we investigated the reaction with respect to the mannosyl donor and the involvement of a glycosyltransferase. C-mannosylation of Trp-7 was reduced 10-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
131
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 33 publications
5
131
0
1
Order By: Relevance
“…In Vitro C-Mannosylation-C-Mannosylation in human RNase 2 and IL-12 can be reproduced in vitro using peptides containing the motif WXXW and a microsome-associated transferase (8,12). The modification in these cases is completely restricted to the first Trp, and replacement of the second by Ala completely abolishes the modification in vitro and in vivo (8,9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Vitro C-Mannosylation-C-Mannosylation in human RNase 2 and IL-12 can be reproduced in vitro using peptides containing the motif WXXW and a microsome-associated transferase (8,12). The modification in these cases is completely restricted to the first Trp, and replacement of the second by Ala completely abolishes the modification in vitro and in vivo (8,9).…”
Section: Resultsmentioning
confidence: 99%
“…After centrifugation the upper, aqueous, phase contained the peptide. The radioactivity in 0.2 ml of the upper phase was determined by scintillation counting (8). For preparative purposes, 10 reactions were performed for 42 h at room temperature (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The addition of C-linked Man to tryptophan is thought to occur in the ER (Doucey et al 1998) and no further modification in the Golgi has been observed to date (Wang et al 2009). The O-fucose glycan of TSP repeats is also initiated in the ER, but it is extended in the Golgi with a single Glc (Kozma et al 2006).…”
Section: O-glycosylationmentioning
confidence: 99%
“…One example is C-mannosylation of tryptophan residues within a WXXW motif. This modification also utilizes dolichol phosphate as the sugar donor (Doucey et al, 1998) and has thus far been found in RNase 2 (Loffler et al, 1996), IL-12, properdin, and other members of the complement protein family (Hofsteenge et al, 1999) (Hartmann andHofsteenge, 2000). C-mannosylation almost certainly occurs in the ER, but its timing and consequences for protein folding and activity are not known.…”
Section: Glycosylationmentioning
confidence: 99%